Pengembangan Student Worksheet Berbasis Kearifan Lokal Berbantuan Qr-Code pada Pembelajaran Tematik Kelas V - Ariyani, Lidia; Mulyono, Dodik; Febriandi, Riduan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT This study aims to develop a printed teaching material product in the form of a Student Worksheet Based on Local Wisdom Assisted by QR-Code in Class V Thematic Learning at SD N 7 Saling Empat Lawang which is valid, practical and effective for use in the learning process. The research method is R&D (Research and Development), with a 4-D development model used for definition, design and development. The results of the study, based on the results of the assessment analysis obtained from the validator of language, materials and media obtained an average score that meets the valid criteria. Then the results of the practical analysis of students and teachers obtained an average score that met the practical criteria. The results of the pretest and posttest analysis of students experienced an increase in learning outcomes. In conclusion, the Student Worksheet based on local wisdom assisted by QR-Code is valid, practical and effective to use in the learning process. Keywords: Development, Student Worksheet, Local Wisdom. QR-Cod